Research design and methods a process approach - Bordens, Kenneth S.; Abbott, Bruce B. (McGraw-Hill, 2022)
Research Design and Methods: A Process Approach takes students through the research process, from getting and developing a research idea, to designing and conducting a study, through analyzing and reporting data. The eleventh edition addresses the change in research practices to supplement or replace null hypothesis significance testing (NHST) with other analytic approaches, including Bayesian analysis. Information on the research process is presented in a lively and engaging way, highlighting the numerous decisions that must be made when designing and conducting research and emphasizing the importance of ethical conduct, both in the treatment of research subjects and in the conduct of research and reporting research results.